Oral Presentations Abstracts: MORAL COMPETENCE, MORAL TEAMWORK, MORAL ACTION – OUTCOMES OF MORAL CASE DELIBERATION IN THE EURO-MCD 2.0 FOR EVALUATING CLINICAL ETHICS SUPPORT - DE SNOO-TRIMP, Janine (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Background: For Moral Case Deliberation (MCD), like any form of Clinical ethics support (CES), it is important to know whether it reaches its presumed goal of supporting healthcare professionals in their ethical challenges. Evaluation is needed to gain insight in the value of MCD. Therefore, the Euro-MCD instrument was developed to assess outcomes of MCD, and has now been revised. The aim of this presentation is to present the revised Instrument: the Euro-MCD 2.0. Methods: The revision process was an iterative dialogue in which field study findings were integrated with theoretical reflections and expert-input. Results: The Euro-MCD 2.0 has three domains: 1) Moral Competence, 2) Moral Teamwork and 3) Moral Action. Moral Competence includes items on moral sensitivity, analytical skills and a virtuous attitude, like ‘I speak up in ethically difficult situations’. Moral Teamwork refers to open dialogue and supportive relationships, for example ‘We feel secure to share emotions in ethically difficult situations’. Moral Action includes items about moral decision-making and responsible care, like ‘We are able to explain and justify our care towards patients and their families’. Discussion: The Euro-MCD 2.0 is shorter and more strongly substantiated by empirical data and theoretical reflections. At the conference, we will reflect on the revision process and the underlying foundations of the domains. The revised instrument helps to get insight in the MCD related outcomes for healthcare professionals in their daily practice. Our research can further improve implementation of MCD and contribute to the research field of evaluation of CES in general.